Polymer solid electrolyte, method for manufacturing polymer solid electrolyte, and lithium ion secondary battery
Patent Information
- Application Number
- JP2023135340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-07
AI Technical Summary
【0019】 本発明によれば、耐熱性および電気化学的安定性に優れる高分子固体電解質、高分子固体電解質の製造方法、および前記高分子固体電解質を含むリチウムイオン二次電池を提供することができる。
Smart Images

Figure 2025030229000007 
Figure 2025030229000008 
Figure 2025030229000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer solid electrolyte, a method for producing a polymer solid electrolyte, and a lithium ion secondary battery. [Background technology]
[0002] In previous research on polymer solid electrolytes, since the ionic conductivity of a composite consisting of polyethylene oxide (PEO) and a metal salt was first reported in 1973, ethylene oxide (EO)-type polyether derivatives have mainly been used as the polymer. Up until now, the ionic conductivity of ether-type polymer solid electrolytes has been increased to 100% to be practically usable levels by suppressing crystallization through grafting or networking of EO chains (see Non-Patent Document 1), improving lithium salts (see Non-Patent Document 2), and filling with inorganic fillers (see Non-Patent Document 3). -4 It has reached the S / cm level.
[0003] However, ether-type polymer solid electrolytes have issues with the lithium ion transport number (the proportion of the current value carried by lithium ions in the total current response to a constant voltage measured) and oxidation resistance (about 4 V). Because the polyether chain and lithium ions form a stable solvation structure, the lithium ion transport number of polymer solid electrolytes is very low at about 0.1 to 0.4, and tends to depend on anion conduction. A decrease in the lithium ion transport number causes polarization of the electrode surface, thereby reducing the performance of batteries that use cations such as lithium ions as the main carrier. Research has been conducted on electrolytes that conduct only lithium ions by fixing the anion structure to the polymer, but this instead causes a decrease in ionic conductivity.
[0004] On the other hand, the present inventor has focused on polyalkylene carbonates, such as polymer solid electrolytes, which overcome the drawbacks of polyethers, and has evaluated the properties of lithium ion secondary batteries. The present inventor has focused on polymers (polyalkylene carbonates) that have, as their backbone units, carbonate structures, which are the main polar sites of organic solvents used in the electrolytes of lithium ion secondary batteries, and has been the first in the world to clarify their potential as novel electrolytes (see Patent Document 1 and Non-Patent Document 4). Such carbonate-type polymer solid electrolytes have a high lithium ion transport number of 0.6 to 0.8 and a low ionic charge transport number of 10 -4 It showed excellent ionic conductivity of 100 S / cm or more (see Non-Patent Document 5) and oxidation resistance of 5 V or more (see Non-Patent Document 6), making it an excellent solid electrolyte. Research on this carbonate-type polymer solid electrolyte has since expanded to include composites with inorganic fillers (see Non-Patent Document 7) and random copolymerization with ethylene oxide (see Non-Patent Document 8). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5610468 [Non-patent literature]
[0006] [Non-Patent Document 1] Takeoka et al., Polym. Adv. Tech., 4, 53 (1993). [Non-Patent Document 2] Armand et al., Electrochim. Acta, 37, 1699 (1992). [Non-Patent Document 3] Scrosati et al., Nature, 394, 456 (1998). [Non-Patent Document 4] Y. Tominaga et al., Polymer, 51, 4295 (2010). [Non-Patent Document 5] Y. Tominaga et al., Chem. Commun., 50, 4448 (2014). [Non-Patent Document 6] K. Kimura et al., J. Polym. Sci. B Polym. Phys., 54, 2442 (2016). [Non-Patent Document 7] Z. Li et al., Polym. Adv. Tech., 29, 820 (2018). [Non-Patent Document 8] Y. Tominaga et al., Electrochim. Acta, 312, 342 (2019). Summary of the Invention [Problem to be solved by the invention]
[0007] Polyethylene oxide and polyether-type polymer solid electrolytes had problems such as low lithium ion transport numbers and low-temperature characteristics due to crystallization of PEO chains. On the other hand, carbonate-type polymer solid electrolytes required a high lithium salt concentration to bring out the electrolyte properties, and as a result, the decrease in mechanical strength as a polymer solid electrolyte was a major issue. Furthermore, a common issue with the above-mentioned polymer solid electrolytes was that the characteristics (discharge capacity, overvoltage, cycleability) of lithium ion secondary batteries were lower than those of lithium ion secondary batteries using conventional electrolytes and all-solid-state batteries using inorganic solid electrolytes, and a significant improvement in charge-discharge cycle characteristics (stabilization of battery capacity against cycle number) was essential, especially for practical use.
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a polymer solid electrolyte having excellent heat resistance and electrochemical stability, a method for producing the polymer solid electrolyte, and a lithium ion secondary battery containing the polymer solid electrolyte. [Means for solving the problem]
[0009] The present invention has the following aspects. [1] A polymer solid electrolyte comprising a polyethylene carbonate derivative represented by the following chemical formula (1), an inorganic filler, and a lithium salt:
[0010] [ka] (In the formula, R may have a substituent and is an acetyl group, a propionyl group, or a phenyl group; n is 100 or more.)
[0011] [2] The polymer solid electrolyte according to [1], wherein the inorganic filler has an average particle size of 1.0 nm or more and 100 μm or less.
[0012] [3] The polymer solid electrolyte according to [1] or [2], wherein the inorganic filler has an aspect ratio of 1 or more and 1,000 or less.
[0013] [4] The polymer solid electrolyte according to any one of [1] to [3], wherein the inorganic filler is at least one selected from aluminum oxide, titanium oxide, silicon oxide, zirconium oxide, zinc oxide, barium oxide, potassium titanate, barium titanate, silicon carbide, and silicon nitride.
[0014] [5] The polymer solid electrolyte according to any one of [1] to [4], wherein the content of the inorganic filler is 0.05 parts by mass or more and 20 parts by mass or less per part by mass of the polymer solid electrolyte.
[0015] [6] The polymer solid electrolyte according to any one of [1] to [5], wherein the content of the lithium salt is 0.5 parts by mass or more and 80 parts by mass or less per part by mass of the polymer solid electrolyte.
[0016] [7] A battery comprising: a positive electrode including a positive electrode active material layer; an electrolyte layer; and a negative electrode including a negative electrode active material layer; The lithium ion secondary battery, wherein the electrolyte layer contains the polymer solid electrolyte according to any one of [1] to [6].
[0017] [8] A method for producing a polymer solid electrolyte, comprising: a step of mixing a polyethylene carbonate derivative represented by the following chemical formula (1), an inorganic filler, and a lithium salt in an organic solvent to prepare a precursor solution; a step of applying the precursor solution onto a substrate to form a coating film; and a step of drying the coating film.
[0018] [ka] (In the formula, R may have a substituent and is an acetyl group, a propionyl group, or a phenyl group; n is 100 or more.) Effect of the Invention
[0019] According to the present invention, it is possible to provide a polymer solid electrolyte having excellent heat resistance and electrochemical stability, a method for producing the polymer solid electrolyte, and a lithium ion secondary battery including the polymer solid electrolyte. [Brief description of the drawings]
[0020] [Figure 1] FIG. 2 is a diagram showing the results of 1H-NMR measurement of the PEC obtained in Example 1. [Diagram 2] FIG. 2 is a diagram showing the results of 1H-NMR measurement of the PEC of Comparative Example 1. [Diagram 3] FIG. 1 is a graph showing the results of measuring the charge-discharge characteristics of the polymer solid electrolyte of Example 2. [Figure 4] FIG. 1 is a graph showing the results of measuring the charge-discharge characteristics of the polymer solid electrolyte of Example 2. [Diagram 5] FIG. 13 is a graph showing the results of measuring the charge-discharge characteristics of the polymer solid electrolyte of Comparative Example 2. [Figure 6] FIG. 13 is a graph showing the results of measuring the charge-discharge characteristics of the polymer solid electrolyte of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] An embodiment of the polymer solid electrolyte, the method for producing the polymer solid electrolyte, and the lithium ion secondary battery of the present invention will be described. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.
[0022] [Polymer solid electrolyte] A polymer solid electrolyte according to one embodiment of the present invention contains a polyethylene carbonate derivative represented by the following chemical formula (1), an inorganic filler, and a lithium salt.
[0023] [ka] (In the formula, R may have a substituent and is an acetyl group, a propionyl group, or a phenyl group; n is 100 or more.)
[0024] The polyethylene carbonate derivatives are those in which the hydroxyl groups (-OH) of polyethylene carbonate are substituted with acetyl groups, propionyl groups or phenyl groups (R shown in the above chemical formula (1)).
[0025] In the above chemical formula (1), n is 100 or more, and preferably 200 or more.
[0026] The polyethylene carbonate derivative can be synthesized as follows. Here, the case where R in the above chemical formula (1) is an acetyl group is taken as an example. Polyethylene carbonate is dissolved in dehydrated acetonitrile to prepare a solution of polyethylene carbonate in dehydrated acetonitrile. Next, pyridine as a reaction catalyst and acetic anhydride as a terminal modifier are added to the dehydrated acetonitrile solution, and these are stirred and mixed at 40° C. for 24 hours. The resulting product is then purified with methanol to obtain the polyethylene carbonate derivative.
[0027] Examples of inorganic fillers include aluminum oxide (Al2O3), titanium oxide (TiO2), silicon oxide (SiO2), zirconium oxide (ZrO2), zinc oxide (ZnO), barium oxide (BaO), potassium titanate (K2O·8TiO2), barium titanate (BaTiO3), silicon carbide (SiC), and silicon nitride (Si3N4). Among these, aluminum oxide, titanium oxide, silicon oxide, zirconium oxide, zinc oxide, barium oxide, and barium titanate are more preferred. These inorganic fillers may be used alone or in combination of two or more.
[0028] The inorganic filler preferably has an average particle size of 1.0 nm to 100 μm, more preferably 10 μm or less, and even more preferably 5.0 μm or less.
[0029] The average particle size of the inorganic filler can be measured by particle size distribution measurement, zeta potential measurement, and scanning electron microscope measurement.
[0030] In order to increase film strength with a small amount of inorganic filler, a fibrous or plate-like shape such as whiskers is preferred, and when using such inorganic fillers, the aspect ratio is usually preferably 2 or more and 1,000 or less, more preferably 5 or more and 800 or less, and even more preferably 10 or more and 500 or less.
[0031] The aspect ratio of the inorganic filler can be measured by particle size distribution measurement or scanning electron microscope measurement.
[0032] The content of the inorganic filler is preferably 0.05 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 10 parts by mass, per part by mass of the polymer solid electrolyte.
[0033] Examples of the lithium salt include lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). These lithium salts may be used alone or in combination of two or more.
[0034] The content of the lithium salt is preferably from 0.5 to 80 parts by mass, and more preferably from 1 to 60 parts by mass, per part by mass of the polymer solid electrolyte.
[0035] The polymer solid electrolyte of this embodiment contains a polyethylene carbonate derivative represented by the above chemical formula (1), an inorganic filler, and a lithium salt. Therefore, in a lithium ion secondary battery using the polymer solid electrolyte of this embodiment, the thermal and electrical instability caused by backbiting of polyethylene carbonate is suppressed by substituting the terminal hydroxyl groups of the polyethylene carbonate with acetyl groups, propionyl groups, or phenyl groups, and the heat resistance and electrochemical stability of the polyethylene carbonate derivative are improved, resulting in improved charge-discharge cycle performance.
[0036] [Method of manufacturing polymer solid electrolyte] The method for producing the polymer solid electrolyte of the present embodiment includes a step of mixing the polyethylene carbonate derivative represented by the above chemical formula (1), an inorganic filler, and a lithium salt in an organic solvent to prepare a precursor solution (hereinafter referred to as the "preparation step"), a step of applying the precursor solution onto a substrate to form a coating film (hereinafter referred to as the "coating film formation step"), and a step of drying the coating film (hereinafter referred to as the "drying step").
[0037] In the preparation step, the polyethylene carbonate derivative, the inorganic filler, and the lithium salt are added to an organic solvent so that each component has a predetermined content, and mixed using a bead mill, a ball mill, an attritor, a planetary centrifugal mixer, an ultrasonic disperser, or the like to prepare a precursor solution.
[0038] As the organic solvent, for example, acetonitrile, dimethylformamide, dimethylsulfoxide, 1,4-dioxane, chloroform, 1,2-dichloroethylene, etc. can be used.
[0039] In the coating film forming step, a coating film made of the precursor solution is formed on a substrate such as a Teflon (registered trademark) sheet. As a method for forming the coating film, for example, a coating film having a uniform thickness can be formed on the substrate using a coating machine such as a roll coater, a blade coater, or a bar coater.
[0040] In the drying step, the coating film formed on the substrate is dried using an infrared heater, a hot air dryer, a heated vacuum dryer, etc. In order to efficiently remove the remaining solvent after drying, it is preferable to heat the substrate from the back side.
[0041] Furthermore, in cases where voids are generated in the film of the polymer solid electrolyte to be formed when the solvent is evaporated during drying, or when it is desired to control the orientation of the added inorganic filler having an aspect ratio, a heating and pressurizing treatment such as a calendaring treatment may be performed during the drying step.
[0042] According to the method for producing a polymer solid electrolyte of the present embodiment, the above-mentioned polymer solid electrolyte can be obtained.
[0043] [Lithium-ion secondary battery] The lithium ion secondary battery of the present embodiment includes a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer. The electrolyte layer includes the polymer solid electrolyte of the above embodiment.
[0044] The positive electrode has a positive electrode current collector and a positive electrode active material layer formed on one main surface of the positive electrode current collector.
[0045] The positive electrode current collector may be, for example, aluminum foil.
[0046] The positive electrode active material layer contains a positive electrode active material such as lithium iron phosphate, and a binder such as polyvinylidene fluoride.
[0047] The negative electrode has a negative electrode current collector and a negative electrode active material layer formed on one main surface of the negative electrode current collector.
[0048] The negative electrode current collector may be, for example, copper foil.
[0049] The negative electrode active material layer contains a negative electrode active material such as natural graphite, and a binder such as styrene-butadiene rubber or carboxymethyl cellulose.
[0050] According to the lithium ion secondary battery of the present embodiment, since the electrolyte layer contains the polymer solid electrolyte of the above-mentioned embodiment, the battery has excellent charge / discharge cycle properties. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0052] [Example 1] 1 g of PEC was added to 10 mL of dehydrated acetonitrile (Kanto Chemical Co., Ltd., purity 99.5%) and gently stirred for 3 hours to dissolve the PEC in the dehydrated acetonitrile, thereby preparing a PEC solution. Next, acetic anhydride (Tokyo Chemical Industry Co., Ltd., purity 99.0%) was added as a terminal modifier and pyridine (Wako Pure Chemical Industries, Ltd., purity 99.5%) was added as a reaction catalyst to the obtained PEC solution, and the solution was stirred at 40°C for 48 hours to convert the terminals of the PEC to acetate. 3 mL of the deuterated chloroform solution containing the product was taken out, and a specified amount of tetramethylsilane was added as an internal standard substance. 1 H-NMR was measured. The results are shown in Figure 1. For comparison (Comparative Example 1), 1 H-NMR was measured in the same manner, and the results are shown in Figure 2. As a result, it was confirmed that a PEC derivative with an acetate terminal (PEC-Ac) was obtained, and the yield of the PEC derivative was 65%. 1For the H-NMR measurement, a 400 MHz nuclear magnetic resonance apparatus manufactured by JEOL Ltd. was used. The obtained compound 1 The H-NMR measurement data is shown below. 1 H-NMR (400MHz, solvent: CDCl3): δ(ppm): -CH2-CH2-@4.38ppm, terminal -OC(=O)-CH3@2.09ppm. The molecular weight of the obtained PEC derivative was measured by gel permeation chromatography (GPC) and found to be 41743 (n = approx. 474). The molecular weight of PEC was also measured in the same manner and found to be 38450 (n = approx. 437).
[0053] [Example 2] 0.1 g of the PEC derivative (PEC-Ac) obtained in Example 1, 1.28 g of lithium bis(fluorosulfonyl)imide, and 0.15 g of aluminum oxide (manufactured by Alfa Aesar, average particle size 0.3 μm) were added to 30 mL of acetonitrile and mixed in a planetary centrifugal mixer (manufactured by Thinky Corporation, Awatori Neritarou) to prepare a precursor solution. The obtained precursor solution was applied onto a Teflon (registered trademark) substrate to form a coating film. The coating was dried in a heating vacuum dryer at 60° C. for 24 hours to obtain a polymer solid electrolyte. For comparison (Comparative Example 2), a polymer solid electrolyte containing 1.28 g of lithium bis(fluorosulfonyl)imide and 0.15 g of aluminum oxide (manufactured by Alfa Aesar, average particle size 0.3 μm) per 0.1 g of PEC (PEC-OH) was similarly produced.
[0054] "Charge / discharge characteristics measurement" The charge and discharge characteristics of the polymer solid electrolyte of Example 2 were measured. HJ1020mSD8 (product name) manufactured by Hokuto Denko Corporation was used. The measurement conditions were a measurement temperature of 40°C and a charge and discharge rate of 1 / 20C. A CR2032 coin cell was used as the measurement cell. The results are shown in Figures 3 and 4. From the results shown in FIG. 3, it was found that the polymer solid electrolyte of Example 2 had a stable charge / discharge curve, and the cycle dependency of the discharge capacity and the coulombic efficiency was also significantly improved. 4, it was found that the polymer solid electrolyte of Example 2 did not show any decrease in discharge capacity from the 1st cycle to the 8th to 10th cycles, and showed almost no decrease in capacity up to the 10th cycle. Furthermore, it was found that the capacity retention rate from the 1st cycle to the 10th cycle was 96%.
[0055] The charge / discharge characteristics were similarly measured for Comparative Example 2. From the results shown in Figures 5 and 6, it was found that the polymer solid electrolyte of Comparative Example 2 had an unstable charge / discharge curve, and the cycle dependency of the discharge capacity gradually decreased. [Industrial Applicability]
[0056] INDUSTRIAL APPLICABILITY The present invention can provide a polymer solid electrolyte having excellent heat resistance and electrochemical stability, and can contribute to increasing the capacity and efficiency of lithium ion secondary batteries.
Claims
1. A polymer solid electrolyte comprising a polyethylene carbonate derivative represented by the following chemical formula (1), an inorganic filler, and a lithium salt: 【Chemistry 1】 (In the formula, R may have a substituent and is an acetyl group, a propionyl group, or a phenyl group; n is 100 or more.)
2. The polymer solid electrolyte according to claim 1 , wherein the inorganic filler has an average particle size of 1.0 nm or more and 100 μm or less.
3. The polymer solid electrolyte according to claim 1 , wherein the inorganic filler has an aspect ratio of 1 or more and 1,000 or less.
4. 2. The polymer solid electrolyte according to claim 1, wherein the inorganic filler is at least one selected from the group consisting of aluminum oxide, titanium oxide, silicon oxide, zirconium oxide, zinc oxide, barium oxide, potassium titanate, barium titanate, silicon carbide, and silicon nitride.
5. 2. The polymer solid electrolyte according to claim 1, wherein the content of the inorganic filler is 0.05 parts by mass or more and 20 parts by mass or less per 1 part by mass of the polymer solid electrolyte.
6. 2. The polymer solid electrolyte according to claim 1, wherein the content of the lithium salt is 0.5 parts by mass or more and 80 parts by mass or less per 1 part by mass of the polymer solid electrolyte.
7. a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer; A lithium ion secondary battery, wherein the electrolyte layer comprises the polymer solid electrolyte according to any one of claims 1 to 6.
8. A step of mixing a polyethylene carbonate derivative represented by the following chemical formula (1), an inorganic filler, and a lithium salt in an organic solvent to prepare a precursor solution; applying the precursor solution onto a substrate to form a coating film; and drying the coating film. 【Chemistry 2】 (In the formula, R may have a substituent and is an acetyl group, a propionyl group, or a phenyl group; n is 100 or more.)
Citation Information
Patent Citations
Printer
JP1981010468A